2017
DOI: 10.1093/rof/rfx047
|View full text |Cite
|
Sign up to set email alerts
|

Finance, Comparative Advantage, and Resource Allocation*

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 101 publications
0
3
0
Order By: Relevance
“…This theory was put forward by David Ricardo. In this theory, he states that international trade or exports can occur if there are differences in comparative advantages of each country (Abiad and Teipelke, 2017;Alami, 2017, Bansal et al, 2017, Jaud et al, 2018, Murdock, 2019and Davis and Dingel, 2020. Comparative advantage can be achieved if a country is able to produce a number of goods with a large volume but at a lower cost compared to other countries.…”
Section: Theory Of Comparative Advantagementioning
confidence: 99%
“…This theory was put forward by David Ricardo. In this theory, he states that international trade or exports can occur if there are differences in comparative advantages of each country (Abiad and Teipelke, 2017;Alami, 2017, Bansal et al, 2017, Jaud et al, 2018, Murdock, 2019and Davis and Dingel, 2020. Comparative advantage can be achieved if a country is able to produce a number of goods with a large volume but at a lower cost compared to other countries.…”
Section: Theory Of Comparative Advantagementioning
confidence: 99%
“…Countries tend to concentrate their exports because of imperfect and incomplete access to finance (DeRosa, 1992;Acemoglu and Zilibotti, 1997). While other studies find that comparative advantage is another reason for export concentration (Saint-Paul, 1992;Jaud et al, 2012). According to Ruffin (1974), a country diversifies its exports to evade the uncertainty in the general price of goods and trade.…”
Section: Jel Classification -F1 F3 C23mentioning
confidence: 99%
“…This literature has shown that a well-developed and functioning financial environment is key for countries' and firms' export success. In particular, domestic financial development improves export performance, especially for industries dependent on external finance and firms facing credit constraints (e.g., Beck, 2002Beck, , 2003Becker, Jinhzu, & Greenberg, 2013;Berman & Hericourt, 2010;Besedes, Byung-Cheol, & Lugovskyy, 2014;Greenaway, Guariglia, & Kneller, 2007;Jaud, Kukenova, & Strieborny, 2009, 2017Ju & Wei, 2005;Manova, 2007Manova, , 2013. A related strand of papers has explored the negative impact of shocks to the financial system on trade performance, especially during the recent global financial crisis (e.g., Abiad, Mishra, & Topalova, 2014;Amiti & Weinstein, 2011;Baldwin, 2009;Bems, Johnson, & Yi, 2013;Berman and Martin, 2012;Bricongne, Fontagn e, Gaulier, Taglioni, & Vicard, 2012;Chor & Manova, 2012;Kiendrebeogo, 2013;Levchenko, Lewis, & Tesar, 2010;Paravisini, Rappoport, Schnabl, & Wolfenzon, 2015).…”
mentioning
confidence: 99%